Prognostic relevance of circulating endothelial progenitor cells in patients with chronic heart failure - Koller, Lorenz; Hohensinner, Philipp; Sulzgruber, Patrick; Blum, Steffen; Maurer, Gerald; Wojta, Johann; Hülsmann, Martin; Niessner, Alexander (Thrombosis and Haemostasis, 2016)
Novel strategies for a tailored risk prediction in chronic heart failure (CHF) are crucial to identify patients at very high risk for an improved patient management and to specify treatment regimens. Endothelial progenitor cells (EPCs) are an important endogenous repair mechanism with the ability to counteract endothelial injury and the possibility of new vessel formation. We hypothesised that exhaustion of circulating EPCs may be a suitable prognostic biomarker in patients with CHF. EPCs, defined as CD34+CD45dimKDR+ cells, were analysed using fluorescence-activated cell sorting. EPCs were measured in 185 patients with CHF including 87 (47%) patients with ischaemic aetiology and 98 (53%) patients with non-ischaemic CHF and followed for a median time of 2.7 years. During this period, 34.7% of patients experienced the primary study endpoint all-cause mortality. EPC count was a significant and independent inverse predictor of mortality with an hazard ratio hazard ratio (HR) per increase of one standard deviation (1-SD) of 0.47 (95% confidence interval [CI]: 0.35–0.61; p<0.001) and remained significant after multivariable adjustment for a comprehensive set of cardiovascular risk factors and potential confounders with a HR per 1-SD of 0.54 (95% CI: 0.4–0.73; p<0.001). EPCs further demonstrated additional prognostic information indicated by improvements in C-statistic, net reclassification index and integrated discrimination increment. In conclusion, in our study circulating EPCs turned out as strong and independent inverse predictors of mortality underlining the importance of an impaired endothelial repair mechanism in the pathophysiology and progression of CHF.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Ischaemic heart disease; outcome; vasculogenesis